Pervasive Misclassification and Misconception of Study Designs in Asian Dermatology Journals Listed in Science Citation Index-Expanded - Choi, Sungjun; Yoon, Hyun-Sun (Annals of dermatology, 2020)
Misclassification of study designs of journals can hinder the readers from assessing the strengths and weaknesses of the study and evaluating the applicability of the study in the real-world setting. However, it seems that it is common for authors to neglect to classify the study design. We aimed to evaluate the accuracy of the classification of study designs and examine the common errors. This descriptive study analyzed four Asian dermatology journals listed in the science citation index expanded from January 2018 to December 2018. We investigated discrepancies between author-reported and actual study designs. Design Algorithm for Medical Literature on Intervention (DAMI) was used to determine the actual study design. Of the 177 papers analyzed, only 72 articles (40.7%) revealed their study design and among them, 23 articles (32.0%) showed discrepancies between the author-reported and the actual study designs. Case-control studies were the most commonly misclassified study designs by authors. There were considerable differences between the author-reported study design and the actual study design in Asian dermatology journals. Proper classification of study designs by the authors is essential to strengthen evidencebased medicine.